2005
DOI: 10.1016/j.jvs.2005.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Vascular risk factors and diabetic neuropathy

Abstract: backgroundOther than glycemic control, there are no treatments for diabetic neuropathy. Thus, identifying potentially modifiable risk factors for neuropathy is crucial. We studied risk factors for the development of distal symmetric neuropathy in 1172 patients with type 1 diabetes mellitus from 31 centers participating in the European Diabetes (EURODIAB) Prospective Complications Study. methodsNeuropathy was assessed at baseline (1989 to 1991) and at follow-up (1997 to 1999), with a mean (±SD) follow-up of 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
180
5
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(204 citation statements)
references
References 12 publications
(16 reference statements)
13
180
5
6
Order By: Relevance
“…20 21 Indeed a recent study suggested that modification of lipid abnormalities may influence progression of diabetic neuropathy. 22 Vitamin B1 and B6 levels are not measured routinely in patients with neuropathy primarily because such deficiencies have been linked to readily identified conditions, notably alcoholism, malabsorption syndromes, or malnutrition. 19 However, others have documented low B1 and B6 levels in the absence of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…20 21 Indeed a recent study suggested that modification of lipid abnormalities may influence progression of diabetic neuropathy. 22 Vitamin B1 and B6 levels are not measured routinely in patients with neuropathy primarily because such deficiencies have been linked to readily identified conditions, notably alcoholism, malabsorption syndromes, or malnutrition. 19 However, others have documented low B1 and B6 levels in the absence of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study 23.5% developed neuropathy, which apart from the glycaemic control was related to potentially modifiable cardiovascular risk factors including raised serum triglyceride, body mass index, smoking, and hypertension. 34 A stepwise progressive study of treatment of type II diabetic patients with hypotensive drugs, angiotensin converting enzyme inhibitors, calcium channel blockers, hypoglycaemic agents, aspirin, hypolipidaemic agents, and antioxidants. This study argues for the multifactorial nature of neuropathy and need for managing multiple metabolic abnormalities.…”
Section: Association Of Vascular Risk Factors With Dnmentioning
confidence: 99%
“…Autonomic neuropathy is found to be present in over 20% of patients with type 1 diabetes when assessed 7 years after diagnosis 1. In healthy subjects, there is a rapid early rise in heart rate upon standing which falls over approximately 30 beats to relative bradycardia.…”
Section: Differential Diagnosismentioning
confidence: 99%